IMPACT OF CLIMATE CHANGE & ENVIRONMENTAL DISCLOSURE ON FINANCIAL PERFORMANCE: EVIDENCE FROM PAKISTAN - Mustansar Hayat; Asad Ali; Zulfiqar Ali; Basharat Khan (International Journal of Contemporary Issues in Social Sciences, 2024)
We explore the relationship between climate change and environmental (CCE) disclosure and the financial performance of non-financial companies listed on the KSE-100 index in Pakistan. Recognizing the growing importance of environmental, social, and governance (ESG) factors, the study investigates the impact of CCE disclosure on financial indicators such as Tobin’s Q. The research also introduces the moderating role of company size in this relationship. Using a mix of qualitative and quantitative methods, the study analyzes data from annual reports of 62 firms for the years 2021-2023. The findings suggest a positive association between CCE disclosure and financial performance, with a non-linear relationship observed. Additionally, the study highlights the moderating effect of company size on this relationship. The significance of the study lies in its contribution to understanding the decision-making value of CCE information for stakeholders in Pakistan. Recommendations include increased awareness of corporate social responsibility and continued enhancement of legislative laws governing CCE disclosures.